2007
DOI: 10.1158/0008-5472.can-07-0273
|View full text |Cite
|
Sign up to set email alerts
|

Born to Be Exported: COOH-Terminal Nuclear Export Signals of Different Strength Ensure Cytoplasmic Accumulation of Nucleophosmin Leukemic Mutants

Abstract: Creation of a nuclear export signal (NES) motif and loss of tryptophans (W) 288 and 290 (or 290 only) at the COOH terminus of nucleophosmin (NPM) are both crucial for NPM aberrant cytoplasmic accumulation in acute myelogenous leukemia (AML) carrying NPM1 mutations. Hereby, we clarify how these COOH-terminal alterations functionally cooperate to delocalize NPM to the cytoplasm. Using a Rev(1.4)-based shuttling assay, we measured the nuclear export efficiency of six different COOH-terminal NES motifs identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 40 publications
11
116
0
1
Order By: Relevance
“…Interaction of Crm1 (exportin 1) with the two NPM1wt N-terminus NES motifs 13,14 (which presumably occurs both in nucleoplasm and nucleolus) ensures NPM1wt nuclear export. Using a Rev(1.4)-based shuttling assay, we found that both NPM1wt NES motifs have low export efficiency 41 and, therefore, little native protein is exported from nucleus to cytoplasm. As NLS-mediated nuclear import of NPM1wt greatly predominates over export, 41 most NPM1wt resides within the nucleolus (Figure 2).…”
Section: Native Npm1 Is a Nucleolar Protein With Ubiquitous Tissue Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of Crm1 (exportin 1) with the two NPM1wt N-terminus NES motifs 13,14 (which presumably occurs both in nucleoplasm and nucleolus) ensures NPM1wt nuclear export. Using a Rev(1.4)-based shuttling assay, we found that both NPM1wt NES motifs have low export efficiency 41 and, therefore, little native protein is exported from nucleus to cytoplasm. As NLS-mediated nuclear import of NPM1wt greatly predominates over export, 41 most NPM1wt resides within the nucleolus (Figure 2).…”
Section: Native Npm1 Is a Nucleolar Protein With Ubiquitous Tissue Exmentioning
confidence: 99%
“…Using a Rev(1.4)-based shuttling assay, we found that both NPM1wt NES motifs have low export efficiency 41 and, therefore, little native protein is exported from nucleus to cytoplasm. As NLS-mediated nuclear import of NPM1wt greatly predominates over export, 41 most NPM1wt resides within the nucleolus (Figure 2). In contrast, the rare NPM1.2 (or B23.2) truncated isoform localizes to nucleoplasm, 8 as it lacks the C-terminus nucleolar-binding domain and cannot, therefore, bind efficiently to the nucleolus.…”
Section: Native Npm1 Is a Nucleolar Protein With Ubiquitous Tissue Exmentioning
confidence: 99%
“…This new NES is added to and reinforces the two NES normally present in the N-terminal domain of the native protein. 27 Notably, when only Trp290 is replaced, a stronger NES motif is inserted to ensure maximal export in Figure 3. Mutations at the C-terminal domain are associated with acute myeloid leukemia.…”
Section: Aml-associated Npm1 Mutations: Implications For Protein Stabmentioning
confidence: 99%
“…27 Very rarely, mutations may occur at exon XI of NPM1 leading to a mutant protein that is truncated at its C-terminus and lacks both tryptophans. 28 The combined effect of the loss of either one or both tryptophan residues and the appearance of a new NES in the variant protein is mandatory to completely alter the shuttling properties of the protein.…”
Section: Aml-associated Npm1 Mutations: Implications For Protein Stabmentioning
confidence: 99%
See 1 more Smart Citation